2018
DOI: 10.12944/crnfsj.6.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Melon (Momordica charantia L) Fruit Decreased Blood Glucose Level and Improved Lipid Profile of Streptozotocin Induced Hyperglycemia Rats

Abstract: Bitter melon (Momordica charantia, L) is a fruit that traditionally believe has benefits on health. The objective of this study is to identify bitter melon bioactive and nutritional compounds, and their effect on blood glucose level and lipid profile of streptozotocin induced hyperglycemia rats. Rats were divided into three group, those were normal group; hyperglycemia group without bitter melon fruit feeding; and hyperglycemia group with bitter melon fruit administration. Hyperglycemia condition was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…In STZ-induced diabetic rats, MC juice reduces the Na + - and K + -dependent absorption of glucose in jejunal brush border membrane vesicles by affecting PI3K [ 30 ]; MC powder [ 59 ] and fresh fruit [ 60 ] when given orally affect glucose absorption due to dietary fiber. Furthermore, MC powder can lower the expression of GLUT2, thus reducing the reabsorption of glucose by the kidneys and increasing the excretion of urine sugar [ 61 ] ( Figure 2 ).…”
Section: Antidiabetic Efficacy and Mechanism Of Momordicmentioning
confidence: 99%
“…In STZ-induced diabetic rats, MC juice reduces the Na + - and K + -dependent absorption of glucose in jejunal brush border membrane vesicles by affecting PI3K [ 30 ]; MC powder [ 59 ] and fresh fruit [ 60 ] when given orally affect glucose absorption due to dietary fiber. Furthermore, MC powder can lower the expression of GLUT2, thus reducing the reabsorption of glucose by the kidneys and increasing the excretion of urine sugar [ 61 ] ( Figure 2 ).…”
Section: Antidiabetic Efficacy and Mechanism Of Momordicmentioning
confidence: 99%
“…M. charantia contains triterpenoids 11,39,47 , saponins 48 , polypeptides 49 , flavonoids 14,50,51 , alkaloids 40,52,53 and sterols 13,[54][55][56] , which are distributed throughout the entire plant. The seed is not edible, it contains extractable oils, mostly a conjugated triene cis-9, trans-11, trans-13 (c9, t11, t13) conjugated isomer of linolenic acid, known as α-elestearic acid (α-ESA).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…50,58 Several bioactive compounds of the fruit of M. charantia have been registered in the literature; they are classified into carbohydrates, proteins, lipids and more. 46,56,59 Cucurbitane-type triterpenoids such as charantin have been related to antimicrobial activity. 60 Charantin is a 1:1 mixture of two steroidal saponins ( Figure 3), stigmasterol glycoside and β-sitosterol glycoside.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Interest in the antidiabetic activity of M. charantia L. started in the 1940s, where Rivera and colleagues found the hypoglycemic activity of crude extract of M. charantia L. in rabbits [13]. Later, several in vivo studies showed significant glucose lowering potential of whole fruits, fruit pulp, and seeds [14][15][16][17][18]. Based on these significant results of in vivo preclinical studies, a handful of clinical trials were conducted [10]; however, the majority of these trials failed to establish benefits of M. charantia L. in a systematic review conducted in 2014 [19].…”
Section: Introductionmentioning
confidence: 99%